INVENTARISASI DAN IDENTIFIKASI PENYEBAB PENYAKIT PADA Acacia auriculiformis DI YOGYAKARTA - Nur Hidayati; Rina Laksmi Hendrati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Acacia auriculiformis is a fast growing species mostly planted in marginal lands with less intensive in cultivation. Problems found on A. auriculiformis cultivation include disease attacks which then caused a significant economic reduction on the plantation. The aim of this study is to determine causes, intensity and severity of the diseases attacking A. auriculiformis plants. The research was conducted on two observation plots, in the nursery and in clonal bank area established in Yogyakarta. Genetic materials planted in the plots were collected from clonally propagated of trees selected in second generation progeny trial of A. auriculiformis established in Wonogiri, Central Java. Observations of disease signs and symptoms in the two plots were undertaken with 100% plants inventories in rainy and dry seasons. Postulate Koch was then performed on this study to identify the pathogens. The result showed that the powdery mildew caused by Oidium sp. is a dominant disease attacking 100% A. auriculiformis both in the nursery and on clonal bank areas, occurring not only during the rainy season but also during the dry season. There were also other diseases attacking A. auriculiformis namely black mildew caused by Meliola sp, phomopsis, leaf spot disease caused by Phomopsis sp. and root rot disease caused by Ganoderma steyaertanum.